(3EXgGQ GdCSQGQs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI Ydi eMeO hBdg CLeYjfhHYO agPg QSGdI ajeG jMJGL Edjg cd eYQH CTO GdGMJjGL hgh KdGKI CTjGA GdYGed hGdeYehd hGdYed Cj GdEYQGH ahLH JQJjHgG Ydi KdGKI CHhGHs
(3BNQgG (B:s
(3hUaI GSe (B((3dG(B) (3GdeHfj GdeaQO GdeJUdI Hg , aEfg jLhR HfGDgG Ydi GdaJM fMh dG QLd XQja hEYQGHgG QaYG hfUHG fMh dG QLd XQja hXQjaGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 61s
(3eYLe GdeDdajf(B: 3 / 176s
(3cTa GdXfhf(B: 1 / 117s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs